2018
DOI: 10.3389/fpls.2017.02191
|View full text |Cite
|
Sign up to set email alerts
|

A Community-Based Culture Collection for Targeting Novel Plant Growth-Promoting Bacteria from the Sugarcane Microbiome

Abstract: The soil-plant ecosystem harbors an immense microbial diversity that challenges investigative approaches to study traits underlying plant-microbe association. Studies solely based on culture-dependent techniques have overlooked most microbial diversity. Here we describe the concomitant use of culture-dependent and -independent techniques to target plant-beneficial microbial groups from the sugarcane microbiome. The community-based culture collection (CBC) approach was used to access microbes from roots and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 75 publications
2
81
0
4
Order By: Relevance
“…Due to their absence in the bulk soil, we can speculate that members of the Moraxellaceae family are true endophytes that can be transmitted from the seeds to the root endosphere. This family has been previously discovered in root environments and several genera of the Moraxellaceae are known to promote plant growth [45][46][47]. Secondly, the family Flavobacteriaceae was detected in the root endosphere of both soil-and in vitro-grown maize and additionally, also in the bulk soil samples.…”
Section: Discussionmentioning
confidence: 83%
“…Due to their absence in the bulk soil, we can speculate that members of the Moraxellaceae family are true endophytes that can be transmitted from the seeds to the root endosphere. This family has been previously discovered in root environments and several genera of the Moraxellaceae are known to promote plant growth [45][46][47]. Secondly, the family Flavobacteriaceae was detected in the root endosphere of both soil-and in vitro-grown maize and additionally, also in the bulk soil samples.…”
Section: Discussionmentioning
confidence: 83%
“…Members of these dominant groups, named the core microbiome, can be incorporated in SynComs, thus preventing the lack of efficiency and prevalence observed in situations where strains are outcompeted by naturally occurring microbiota. Notably, studies using both abundant and prevalent core microbes in SynComs have shown efficient colonization and beneficial effects such as plant defense against pathogens and root growth ( Niu et al, 2017 ; Armanhi et al, 2018 ). These studies confirm that core microbial groups are extremely efficient at colonizing plants, highlighting that dominant groups are likely involved in functions important for plant growth and survival.…”
Section: Identifying Relevant Microbes With Key Traits For Stable Andmentioning
confidence: 99%
“…S2). To verify their functions, new cultivation and screening strategies, such as optimization of the culture medium (54) and conditions (55) or multiple in vitro tests involved in different suppressive mechanisms, should be considered.…”
Section: Discussionmentioning
confidence: 99%